2021
DOI: 10.1016/j.lanepe.2021.100030
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction incidence during national lockdown in two French provinces unevenly affected by COVID-19 outbreak: An observational study

Abstract: Background A reduction of admission for MI has been reported in most countries affected by COVID-19. No clear explanation has been provided. Methods To report the incidence of myocardial infarction (MI) admission during COVID-19 pandemic and in particular during national lockdown in two unequally affected French provinces (10-million inhabitants) with a different media strategy, and to describe the magnitude of MI incidence changes relative to the incidence of COVID-19-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
2
14
1
Order By: Relevance
“…This could be a sign of postponed ED presentation or collateral damage. These findings are in line with other studies reporting decreased numbers of hospital admissions and ED presentations with acute coronary syndrome and MI during the first pandemic wave [ 10 12 , 16 , 26 29 ]. There was no clear trend for a compensatory increase after the initial lockdown in 2020.…”
Section: Discussionsupporting
confidence: 92%
“…This could be a sign of postponed ED presentation or collateral damage. These findings are in line with other studies reporting decreased numbers of hospital admissions and ED presentations with acute coronary syndrome and MI during the first pandemic wave [ 10 12 , 16 , 26 29 ]. There was no clear trend for a compensatory increase after the initial lockdown in 2020.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports, we observed a decrease in hospitalisations for AMI and heart failure (figure 3B). Studies worldwide have reported a significant decrease in admissions for cardiovascular diseases during the pandemic 11 32 33. While studies from the USA and Europe reported increased rates of in-hospital mortality,33 34 a study from Japan did not report a notable increase 19.…”
Section: Discussionmentioning
confidence: 93%
“…These elements could be exacerbated during the pandemic, leaving women in a riskier situation. A possible solution to this issue could be rigorous public health campaigns through local media, which proved to be an effective way to promote awareness on the timely care of acute cardiovascular events during the pandemic in the USA and France 23 24…”
Section: Discussionmentioning
confidence: 99%